Small-scale rearing of Anagasta kuehniella for Trichogramma production - Postali Parra, Jose Roberto; Geremias, Leandro Delalibera; Bertin, Aline; Colmenarez, Yelitza C; Coelho, Aloisio (CABI, 2021)
This book contains 4 chapters focusing on techniques for small-scale rearing of the egg parasitoids Trichogramma spp. in the factitious host Anagasta kuehniella [Ephestia kuehniella]. These parasitoids are among the most widely used natural enemies in the world, and in Brazil are used to control lepidopteran pests in a wide variety of crops.